Comparative Evaluation of Packed Bed and Evacuated Tube Collector Solar Dryers for Crop Drying - Hans, V. S.; Singh, Ravneet; Singh, Sukhmeet (Journal of Agricultural Engineering, 2015)
Solar drying of agricultural produce is generally used to overcome the problems associated with open sun drying. An evacuated tube collector solar dryer, having ten evacuated tube collectors connected in parallel, was developed and tested for drying of spinach. Thermal performance in terms of outlet air temperature and drying of spinach were compared with that of a packed bed solar dryer. Parallel evacuated tube collector solar dryer in comparison to packed bed solar dryer performed better in terms of outlet air temperature achieved and amount of moisture removed from spinach. Annualized drying cost of parallel evacuated tube collector solar dryer was better as compared to that of the packed bed solar dryer.